2012
DOI: 10.1371/journal.pone.0052067
|View full text |Cite
|
Sign up to set email alerts
|

Daily Life Stress and the Cortisol Awakening Response: Testing the Anticipation Hypothesis

Abstract: The cortisol awakening response (CAR) is a distinct facet of the circadian cortisol rhythm associated with various health conditions and risk factors. It has repeatedly been suggested that the CAR could be a result of the anticipated demands of the upcoming day (stress anticipation) and could support coping with daily life stress. In a sample of 23 healthy participants CARs were assessed on two consecutive days by measures of salivary cortisol upon awakening (S1) and 30 and 45 minutes later, which were aggrega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 49 publications
4
87
4
Order By: Relevance
“…2) In contrast to the cortisol response to acute exogenous stressors described above, the rapid increase in cortisol normally seen within the 30 minute period after awakening may reflect endogenous diurnal activation of the HPA axis, potentially signifying a readiness to respond to (or cope with) the stress of the upcoming day. Higher increases in the Cortisol Awakening Response (CAR) are associated with attenuated levels of distress in response to daily life stressors in healthy controls (Powell and Schlotz, 2012). In FEP the CAR is blunted (Mondelli et al, 2010a), potentially interacting with cannabis misuse (Monteleone et al, 2014).…”
Section: Evidence Contradicting Hyperactivationmentioning
confidence: 99%
“…2) In contrast to the cortisol response to acute exogenous stressors described above, the rapid increase in cortisol normally seen within the 30 minute period after awakening may reflect endogenous diurnal activation of the HPA axis, potentially signifying a readiness to respond to (or cope with) the stress of the upcoming day. Higher increases in the Cortisol Awakening Response (CAR) are associated with attenuated levels of distress in response to daily life stressors in healthy controls (Powell and Schlotz, 2012). In FEP the CAR is blunted (Mondelli et al, 2010a), potentially interacting with cannabis misuse (Monteleone et al, 2014).…”
Section: Evidence Contradicting Hyperactivationmentioning
confidence: 99%
“…Although largely untested, the stress anticipation hypothesis is supported by research demonstrating higher CAR during week-days versus week-ends (5153) and during athletic competition days versus non-competition days (54). Further support for the stress anticipation hypothesis is provided by a study of healthy adults that demonstrated an association between a higher CAR and an attenuated stress response to stressors encountered later that same day (55). Our results show that women newly diagnosed with breast cancer exhibit a higher CAR when they report feeling less rested in the morning.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, prior work has shown that a greater CAR is associated with attenuated distress responses to stress (Powell and Schlotz, 2012). Under burnout conditions, however, the HPA axis exhibits hypocortisolism, characterized by a blunted CAR (Chida and Steptoe, 2009; Oosterholt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%